MORTALIDADE POR CAUSAS EXTERNAS E RAÇA/COR DA PELE: uma das expressões das desigualdades sociais - Araujo, Edna Maria de (2007)
Introduction: There has been considerable academic work documenting poor living conditions among the Afro-Brazilian population. However, there are few studies in the health literature that document the role of race/skin color as a contributor to health inequalities. Objectives: This study was conducted to analyze differences in mortality by external causes by race/color in Salvador, Bahia, Brazil during the period 1998-2003. Methods: First, we conducted a literature review on social inequalities in both the US and Brazil. Our inclusion criteria were: studies used race/color as a variable, were published in public health or epidemiologic literature, and were published over the period 1986-2005. Next, we conducted a descriptive study in which we calculated the years of potential life lost (PYLL) due to external causes, stratified by gender, age, type of external cause, and, by race and skin color classification. Finally, we conducted an ecological spatial study with areas equivalent to census tracts as the unit of analysis in Salvador. We used a binomial regression model to test the hypothesis that areas with a majority black male population between the ages of 15-49 years will have the highest proportion of mortality by all external causes and by homicide. Results: Of the 56 American studies and 7 Brazilian articles reviewed, 68% were published between 2002-5, 52 were cross studies, being 11 surveys, 6 were observational studies, 3 ecological and 2 were longitudinal studies. Of these, 60.3 % were population based studies and 39.7% studied the health of specific groups. The variable race/color or ethnicity was positively associated with the outcome studied in 84% of the analytical studies and the observed differences were statistically significant in all of the descriptive studies (where the author used a statistical test). The articles published in the US recognized the limitations of such analyses and have attempted to go beyond mere description of the disparity toward understanding the factors that contribute to these inequalities. On the other hand, the Brazilian literature appears to be at the beginning stage of documenting the existence of these inequalities. In the second study, we found that black males lost 21.8 times more PYLL compared to white men. The observed differences in the indicator PYLL/100.000 inhabitants and in the ratios of that indicator remained the same after the standardization by age. In the third study, we found that areas with the highest burden of mortality for all external causes and for homicide tended to cluster in areas with large proportions of black males age 15-49. (RR 1.18, p=0.03; IC 1.011 1,368) was obtained for the association between the proportion of the male population whose ages range from 15 to 49 years and the mortality rate by all the external causes adjusted by co-variables. Conclusions: We produced empirical evidence that black male population in the age range of 15-49, dies at a higher rate and shows major risk of death for external causes and specifically for homicide. We realize that these studies only reveal small facets of a very complex problem and thus we hope that these results will stimulate discussion about the causes and effects of inequalities on health among blacks in Brazil, and that such research will lead toward the development of public policies, which will address these inequalities.